Improvement of Severe Fatigue Following Nuclease Therapy in Patients With Primary Sjögren's Syndrome: A Randomized Clinical Trial. Issue 1 (22nd November 2020) - Posada, James; Valadkhan, Saba; Burge, Daniel; Davies, Kristen; Tarn, Jessica; Casement, John; Jobling, Kerry; Gallagher, Peter; Wilson, Douglas; Barone, Francesca; Fisher, Benjamin A.; Ng, Wan‐Fai
Abstract : Objective: To assess the safety and efficacy of RSLV‐132, an RNase Fc fusion protein, in a phase II randomized, double‐blind, placebo‐controlled clinical trial in patients with primary Sjögren's syndrome (SS). Methods: Thirty patients with primary SS were randomized to receive treatment with RSLV‐132 or placebo intravenously once per week for 2 weeks, and then every 2 weeks for 12 weeks. Eight patients received placebo and 20 patients received RSLV‐132 at a dose of 10 mg/kg. Clinical efficacy measures included the European League Against Rheumatism (EULAR) Sjögren's Syndrome Disease Activity Index, EULAR Sjögren's Syndrome Patient Reported Index (ESSPRI), Functional Assessment of Chronic Illness Therapy–Fatigue (FACIT‐F), Profile of Fatigue (ProF), and the Digit Symbol Substitution Test (DSST). Results: Patients randomized to receive RSLV‐132 experienced clinically meaningful improvements in the ESSPRI score ( P = 0.27), FACIT‐F score ( P = 0.05), ProF score ( P = 0.07), and DSST ( P = 0.02) from baseline to day 99, whereas patients who received placebo showed no changes in any of these clinical efficacy measures. This improvement was significantly correlated with increased expression of selected interferon‐inducible genes (Pearson's correlations, each P < 0.05). Conclusion: Administration of RSLV‐132 improved severe fatigue, as determined by 4 independent patient‐reported measures of fatigue, in patients with primary SS.